The gestation and culmination of the Manual de Plantas de Costa Rica, a tool for the knowledge and conservation of the neotropical flora - Jiménez Madrigal, Quírico (2022)
The Manual of Plants of Costa Rica has been perhaps the most important work in the field of natural sciences published in Costa Rica in recent decades.  This project, which started in the mid-80s of the previous century and concluded with its eighth volume at the end of 2020, had as its main objective to catalog the plants of Costa Rica, for which it was nourished by a rich history and an intense botanical exploration that was born several centuries ago.  Two Costa Rican institutions, the National Museum of Costa Rica and the National Institute of Biodiversity, opened their doors to the Missouri Botanical Garden so that together they could consolidate and finally conclude this work so valuable for the country, for Costa Ricans and for all of Tropical America. It describes the more than 9 000 species of seed plants in 237 families that occur in the country, although today there are more than 11 000 species if we include the group of ferns and their allies.  This high diversity of plant species in such a small area makes Costa Rica a highly biodiverse country from the floristic point of view.